Pax Russica and Pax Sinica as competitive and complementary visions of imperial order in Eurasia (Economic and Political Thought, 2018)
The article focuses on the process of developing a new Eurasian orderand Russia and China’s contemporary imperial projects in the region. Theauthor asks a few important questions concerning the foundations of bothstates’ perception of Eurasian strategies as well as the level of complementarityand competitiveness of those projects organising the Eurasian space inthe Sino-centric or Russo-centric perspective. The main thesis contains anopinion that Russian-Chinese relations at a given stage and in the foreseeablefuture will tend to harmonisation and relative complementarity, whichis also observed in an attempt to synchronise the Eurasian Economic Unionwith the Chinese idea of reviving the Silk Road joining Europe with Asia.Neither Moscow nor Beijing will expose the conflict of interests and rivalryso characteristic of superpowers. The situation results from the fact that bothstates have a very good understanding that strategic rivalry at a given stage ofdevelopment of their bilateral relations is not advantageous for any of them.This similar perception of the international situation and the will to limit, andperhaps in further future eliminate, the USA’s dominance in Eurasia makean adhesive of Russia and China’s strategic partnership. Chinese and Russianauthorities are aware of the advantage they have in imperial efforts thanks tocomplementarity of potentials and coordination of joint as well as individualactivities on the international arena.
Keywords: Pax Russica, Pax Sinica, Eurasia, China, international order